How Does Financial Inclusion Mediate the Impact of Fintech Usage on Consumer Behavior? - Nurmila Dewi; Rasyidusman Hannamara Furqan (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2025)
This study explores the impact of financial technology (fintech) adoption on financial inclusion, its influence on consumer behavior, and the mediating role of financial inclusion. Employing a quantitative approach through structural equation modeling, data were collected via surveys to examine both direct and indirect relationships among the variables. The results indicate that fintech usage plays a key role in enhancing financial inclusion. In turn, financial inclusion contributes significantly to shaping consumer behavior. However, the direct influence of fintech usage on consumer behavior is moderate and statistically inconclusive. The findings confirm that financial inclusion mediates the relationship between fintech usage and consumer behavior, supporting greater financial access and fostering new financial habits. The study concludes that financial inclusion is essential in translating fintech adoption into meaningful behavioral shifts, underscoring the importance of broader financial access initiatives to fully realize the potential of fintech.